The Effect of Socratic Questioning-Based Student Worksheets on Improving Students’ Critical Thinking Skills - Hayati, Laila; Suyidno, Suyidno; Sauqina, Sauqina; Khairunnisa, Yasmine; NF, Abd Rahman (FKIP Universitas Lampung, 2025)
The Effect of Socratic Questioning-Based Student Worksheets on Improving Students’ Critical Thinking Skills. Objective: The ability to think critically plays an essential role in students' achievement in the 21st century, yet its development in science classroom instruction continues to be insufficient. Science education can be monotonous, the content is often perceived as complex, and students typically lack confidence during discussions. This study investigates the influence of Socratic Questioning-based Student Worksheets (SQ-SW) on the improvement of critical thinking skills among junior high school students regarding excretory system content. The novelty of this study lies in the deliberate integration of Socratic questioning techniques into student workbooks, a topic that has been scarcely explored in previous research. Methods: This study employed a quasi-experimental framework with a Nonequivalent Control Group Design. Participants involved 64 eighth-grade students of SMP Negeri 27 Banjarmasin, Indonesia, selected through purposive sampling. The experimental group used the SQ-SW, while the control group used conventional worksheets. Data were collected through a validated response questionnaire and a critical thinking skills assessment, both of which have been confirmed as valid and reliable. Data were analyzed using a descriptive qualitative approach, normality and homogeneity tests, paired-sample t-tests, and independent-sample t-tests. Findings: The findings indicated that SQ-SW could be efficiently applied with a commendable rating. Students in the experimental group demonstrated notable progress in critical thinking, achieving a moderate N-gain (0.56), whereas the control group achieved only a minimal N-gain (0.11). Four critical thinking dimensions (question formulation, hypothesis creation, self-regulation, and conclusion formation) showed moderate advancement. However, the analytical dimension displayed more constrained growth. Conclusion: The use of SQ-SW significantly influences junior secondary students' mastery of excretory system content and their development of critical thinking. Integrating Socratic questions throughout student worksheets creates a systematic, motivating pedagogical approach that breaks conventional classroom routines while enhancing conceptual depth. This investigation introduces a fresh educational technique adaptable to diverse science subjects and academic stages. Keywords: critical thinking skill, excretory system, science learning, socratic questioning.